The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s12012-021-09644-3
|View full text |Cite
|
Sign up to set email alerts
|

Chia Seed Oil Ameliorates Doxorubicin-Induced Cardiotoxicity in Female Wistar Rats: An Electrocardiographic, Biochemical and Histopathological Approach

Abstract: Doxorubicin (DOX) is a potent anti-cancer antibiotic that was widely used for treatment of various cancers. It produces free radicals which result in extreme dose-limiting cardiotoxicity. This study investigated the cardioprotective potential of chia seed oil, an active polyphenolic nutraceutical against doxorubicin-induced cardiotoxicity in Wistar rats. Twenty-four female Wistar rats were divided into four groups (n = 6) which consist of normal control, DOX control, test-A and test-B group. Animals were proph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…Regarding the effect on oxidative stress, DOX showed a significant decline in the endogenous antioxidant capacity, as evident by a significant reduction in GP serum levels and a remarkable increase in MDA levels, confirming the wellknown hypothesis that free radicals play a significant role in DOX-induced cardiotoxicity, and these results were in line with previous reports (Gammella et al, 2014;Lenihan, 2014;Nebigil and Désaubry, 2018). Moreover, the pretreatment with febuxostat led to a significant increase in GP levels and a substantial decrease in MDA serum, coinciding with different studies (Shim et al, 2017;Ahmed et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the effect on oxidative stress, DOX showed a significant decline in the endogenous antioxidant capacity, as evident by a significant reduction in GP serum levels and a remarkable increase in MDA levels, confirming the wellknown hypothesis that free radicals play a significant role in DOX-induced cardiotoxicity, and these results were in line with previous reports (Gammella et al, 2014;Lenihan, 2014;Nebigil and Désaubry, 2018). Moreover, the pretreatment with febuxostat led to a significant increase in GP levels and a substantial decrease in MDA serum, coinciding with different studies (Shim et al, 2017;Ahmed et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…AST, LDH, CK, and CK-MB are essential serum cardiac biomarkers evaluating myocardial injury [ 30 ]. It has been reported that the serum levels of AST, LDH, CK, and CK-MB raise in ADR-induced cardiomyopathy, which is in line with our results [ 31 ]. HE and Masson staining also showed severe cardiac injury and collagen deposition in myocadiac tissues of ADR-induced cardiomyopathy rats.…”
Section: Discussionsupporting
confidence: 93%
“…Nrf-2 is an essential antioxidative gene that inhibits oxidative stress via upregulation of the intracellular antioxidant enzymes such as HO-1 and GCLM, which promote glutathione (GSH) generation ( 7 ). Increased GSH would scavenge the excess reactive oxygen species (ROS) in DOX-treated cardiomyocytes and inhibit various forms of cell death including apoptosis and necroptosis ( 8 , 9 ). The activation of PI3K/AKT is noteworthy as it was able to increase Nrf-2 and GCLM expression in the heart of DOX-treated mice ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%